Preparation method of TaO / NbAlC composite ammonia gas sensor
Ammonia sensors are prepared through Ta2O5/Nb2AlC composites, which solves the problem of low sensitivity of ammonia sensors in the prior art, and efficient monitoring of trace ammonia is achieved. It is suitable for self-powered monitoring systems in vegetable greenhouses.
Patent Information
- Application Number
- CN202411835594.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The sensitivity of existing ammonia sensors is not high, making it difficult to effectively monitor the concentration of trace ammonia in vegetable greenhouses.
Ammonia sensors are prepared using Ta2O5/Nb2AlC composite materials, and Ta2O5 and Nb2AlC are synthesized through specific process steps, and composited into nano-level composites to form an efficient ammonia sensor film.
It realizes high sensitivity detection of ammonia, has short response time, good selectivity and high stability, and is suitable for self-powered NH3 concentration monitoring system in vegetable greenhouses.
Smart Images

Figure CN119715700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ammonia sensor preparation, and in particular to a Ta 2 O 5 / Nb 2 Preparation method of AlC composite ammonia sensor. Background Art
[0002] The trace amount of ammonia NH3 emitted by the ammonium bicarbonate, urea and organic fertilizers applied in the vegetable greenhouse during decomposition will enter the plant through the stomata of the vegetables, burning the tender shoots and even withering the whole vegetable. Therefore, it is very important to monitor the NH3 concentration in the vegetable greenhouse in real time and ventilate in time to prevent vegetable ammonia poisoning and increase vegetable yield.
[0003] Currently, various types of NH 3 Sensors have been developed, including NH based on resistive device structure 3 Sensors are the fastest growing and most widely researched. 3 The sensor device preparation process is the simplest and the performance is stable. In addition, the sensor signal of the device is easy to collect and process, which is conducive to the miniaturization and integration of the device. Due to the advantages of simple manufacturing process and low cost, various semiconductor metal oxides, such as ZnO, CuO, SnO 2 、MoO 3 , WO 3 、TiO 2 etc., have been reported to be used to make resistive NH 3 Raza et al. synthesized PMMA / RGO / ZnO nanocomposite films using in situ solution polymerization and fabricated NH 3 The sensor can show a stable response when the gas concentration is as low as 10ppm. 2 O 5 ), due to its wide band gap (3.9-5.3eV) and high dielectric constant (>20), has been widely used in capacitor manufacturing and sensors. 3 In terms of sensing, Liu et al. 2 O 5 The sensor developed from the Pt / NP material exhibited good NH 3 Sensing performance, at 1000ppm NH 3 / air gas has a high sensing response of 74.4%. 2 O 5 Preparation of NH 3 The performance of the sensor, such as sensitivity and response time, needs to be further improved.
[0004] Due to its high specific surface area, unique electronic properties and controllability, the two-dimensional material MXene has been hotly studied in the fields of catalysis, sensors and supercapacitors in recent years. Han et al. synthesized GaN / Ti using hydrothermal and nitridation methods. 3 C 2 Tx composite materials, and based on this material developed NH 3 Sensor, GaN / Ti 3 C 2 Tx sensor at 10ppmNH 3 The response / recovery time was 80s / 29s at the concentration. 3 C 2 Compared with Tx, Nb 2 AlC is a new type of MAX phase material with a lower Fermi level, which is more conducive to electron transport. 2 The synthesis of AlC is relatively simple. 2 CT x Compared with other MXene materials, it has excellent structural stability. 2 AlC exhibits higher oxidation resistance and chemical stability in air and high humidity environments, which enables it to maintain a longer life and higher reliability during sensor operation.
[0005] Therefore, a highly sensitive Ta 2 O 5 / Nb 2 Preparation method of AlC composite ammonia sensor. Summary of the invention
[0006] The main purpose of the present invention is to provide a Ta 2 O 5 / Nb 2 The invention discloses a method for preparing an AlC composite ammonia sensor, so as to solve the problem that the ammonia sensor in the prior art has low sensitivity.
[0007] To achieve the above object, the present invention provides a Ta 2 O 5 / Nb 2 The preparation method of the AlC composite ammonia sensor specifically comprises the following steps:
[0008] S1, 10 mL, 1.6 mol NH 4 F aqueous solution and 10 mL, 0.2 mol (NH 4 ) 2 S 2 O 8 The aqueous solution was mixed and stirred for 0.5 h, and 0.4 g (NH 4 )2 SO 4 , to obtain mixture A.
[0009] S2, transfer the mixture A to a 30 mL Teflon high-pressure reactor, put a Ta substrate with a purity of 99.99% into the solution, and obtain a mixture B.
[0010] S3, heating the mixture B to 200°C for 48h to form Ta on the Ta substrate 2 O 5 The membrane was separated from the liquid phase and washed with deionized water to obtain product A, which was dried at room temperature overnight to obtain Ta 2 O 5 .
[0011] S4, Nb was synthesized from 99.9% pure, 4.5μm Nb, 99.8% pure, 12.8μm Al and 99.8% pure, 8.5μm NbC powders. 2 AlC.
[0012] S5, preparation of complex Ta 2 O 5 / Nb 2 AlC.
[0013] S6, using the complex Ta 2 O 5 / Nb 2 Preparation of Ta from AlC 2 O 5 / Nb 2 AlC composite ammonia sensor.
[0014] Furthermore, step S4 specifically includes the following steps:
[0015] S4.1, a mixture C having a molar ratio of Nb:Al:NbC=2:1.2:1 is mixed in ethanol for 24 hours.
[0016] S4.2, in a graphite mold pre-sprayed with a layer of boron nitride BN, uniaxial compaction was performed at 20 MPa, and finally vacuum sintering was performed in a spark plasma sintering system to obtain sample A.
[0017] S4.3, after sintering, cool sample A to room temperature, and use a fine sand high-speed diamond grinding wheel to mechanically process the surface of the sintered sample A to remove the layer contaminated by the carbon sheet, thereby obtaining Nb 2 AlC.
[0018] Furthermore, the processing parameters in step S4.2 are set as follows:
[0019] The heating temperature is 1450℃ and the SPS chamber is evacuated to 10-2 Pa, the heating rate was 100 °C / min, the mechanical pressure was 30 MPa, the external pressure was continuously applied from the beginning to the end of heating, and the heating time was 8 minutes.
[0020] Further, step S5 includes the following steps:
[0021] S5.1, use a volume ratio of 3:1 H 2 SO 4 -HNO 3 The mixture was treated at 60 °C for 5 hours. 2 AlC, Nb 2 AlC surface functionalization;
[0022] S5.2, 100 mg of functionalized Nb 2 AlC was dispersed in 50 mL of ethanol by ultrasonication for 0.5 h to obtain Nb 2 AlC solution; at the same time, 300 mg Ta 2 O 5 Dispersed in a mixture of 140 μL benzyl alcohol and 10 mL anhydrous ethanol and added to Nb 2 AlC solution, solution A is obtained;
[0023] S5.3, pre-purge with nitrogen for 0.5 h to remove dissolved oxygen in solution A and stir for 12 h, then transfer the mixture into a microwave reactor and store at 150 °C for 1 h;
[0024] S5.4, after cooling, filter the precipitate, wash with ultrapure water, and dry in a vacuum oven at 80°C for 8 h to obtain the complex Ta 2 O 5 / Nb 2 AlC.
[0025] Further, step S6 includes the following steps:
[0026] S6.1, Ta 2 O 5 / Nb 2 The AlC solution was dropped onto the polyimide substrate to form a sensing film through interdigital electrodes;
[0027] S6.2, after vacuum drying at 60 °C for 4 h, Ta 2 O 5 / Nb 2 AlC composite ammonia sensor.
[0028] Furthermore, the size of the Ta substrate in step S2 is: 10×10×0.25 mm.
[0029] Furthermore, the prepared Ta2 O 5 / Nb 2 AlC composite ammonia sensor is used in vegetable greenhouse self-powered NH 3 In the concentration monitoring system, NH 3 The concentration monitoring system includes: TENG, rectifier module, buck module, energy storage capacitor, voltage management module, Ta 2 O 5 / Nb 2 AlC composite ammonia sensor, data acquisition module, wireless transmission module and real-time monitoring alarm module, after the rectifier module rectifies the alternating current of TENG into direct current, the step-down module then reduces the voltage and increases the current of TENG, and then stores the electrical energy in the energy storage capacitor, and then transmits the electrical energy to Ta through the voltage management module. 2 O 5 / Nb 2 AlC composite ammonia sensor, data acquisition module, wireless transmission module and real-time monitoring alarm module. The data acquisition module collects Ta 2 O 5 / Nb 2 The monitoring data of the AlC composite ammonia sensor is then transmitted to the real-time monitoring alarm module through the wireless transmission module.
[0030] Furthermore, TENG is a barrel-shaped rotating free-standing structure, TENG includes: a rotor and a stator, the stator includes: a first copper electrode and a second copper electrode, the first copper electrode and the second copper electrode are equal in number and are multiple, the multiple first copper electrodes and the multiple second copper electrodes are distributed in a forked finger-like interval, the multiple first copper electrodes are connected to each other, the multiple second copper electrodes are connected to each other, and the first copper electrodes and the second copper electrodes are both covered on the inner wall of the barrel body of the acrylic base; the rotor is a plurality of capton films, the plurality of capton films are distributed in the shape of fan blades, and the plurality of capton films cover all the copper electrodes, one end of the capton film is connected to the mechanical shaft, and the other end contacts the stator, and the mechanical shaft is located at the center of the barrel body.
[0031] Furthermore, there are 6 first copper electrodes, 6 second copper electrodes, and 4 rotors.
[0032] Furthermore, the diameter of TENG is 16 cm and the length of the barrel is 20 cm.
[0033] The present invention has the following beneficial effects:
[0034] The present invention has developed a self-driven vegetable greenhouse NH 3 Monitoring system, capable of intermittent NH 3 Concentration monitoring and alarm. Ta was prepared based on the physical composite method. 2 O5 / Nb 2 AlC binary nanocomposite materials were prepared and the morphology, lattice structure and molecular structure of the materials were characterized by scanning electron microscopy (SEM), X-ray diffraction (Xrd), Fourier transform infrared spectroscopy (FTIR) and other methods. Based on this material and interdigitated electrodes, NH 3 Sensor. The results of first principle calculation (DFT) prove that Ta 2 O 5 / Nb 2 AlC binary nanocomposite materials are better than Ta 2 O 5 and Nb 2 AlC to NH 3 It has better adsorption performance. This is due to the synergistic effect of binary nanomaterials. The two-dimensional material Nb 2 Large comparative area of AlC to Ta 2 O 5 Provides attachment sites and a large amount of NH 3 The developed freestanding structure barrel-type friction nanogenerator TENG captures the breeze energy in the environment and powers the system. The present invention is a self-powered trace NH 3 Monitoring provides solutions and promotes the rapid development of modern agricultural production. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation of the present invention or the technical solutions in the prior art, the following will briefly introduce the drawings required for the specific implementation or the prior art description. Obviously, the drawings described below are some implementations of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0036] Figure 1 Shows Nb 2 SEM image of AlC material at a resolution of 2 μm.
[0037] Figure 2 Shows Ta 2 O 5 SEM image of the material at a resolution of 2 μm.
[0038] Figure 3 Shows Ta 2 O 5 / Nb 2 SEM image of AlC material at a resolution of 10 μm.
[0039] Figure 4 Shows Ta 2 O 5 / Nb 2 SEM image of AlC material at a resolution of 10 μm.
[0040] Figure 5 Shows Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 XRD patterns of AlC materials.
[0041] Figure 6 Shows Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 Raman spectrum of AlC material.
[0042] Figure 7 Shows Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 FTIR spectrum of AlC material.
[0043] Figure 8 Shows Ta 2 O 5 / Nb 2 AlC sensor in different NH 3 Resistance curves under concentration.
[0044] Fig. 9 Shows Ta 2 O 5 Sensors in different NH 3 Resistance curves under concentration.
[0045] Fig.10 Shows Ta 2 O 5 / Nb 2 AlC sensor in different NH 3 Concentration response curve.
[0046] Fig.11 Shows Ta 2 O 5 Sensors in different NH 3 Concentration response curve.
[0047] Fig.12 Shows Ta 2 O 5 and Ta 2 O 5 / Nb 2 AlC sensor in different NH 3 Fitting curve of the response under concentration.
[0048] Fig.13 Shows Ta 2 O 5 、 2 O 5 / Nb 2 Response / recovery time of AlC sensor at 7 ppm.
[0049] Fig.14 Shows Ta 2 O 5 / Nb 2 Resistance curves of AlC sensor at different temperatures.
[0050] Fig.15 Shows Ta 2 O 5 / Nb 2 Response curves of AlC sensor at different humidity levels.
[0051] Fig.16 Shows Ta 2 O 5 / Nb 2 Response curves of AlC sensor to different gases.
[0052] Fig.17 Shows Ta 2 O 5 / Nb 2 Repeatability test curves of AlC sensor at 1ppm and 11ppm.
[0053] Fig.18 Shows Ta 2 O 5 / Nb 2 AlC sensor in different NH 3 Stability curves at different concentrations.
[0054] Fig.19 Shows Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 Adsorption of NH on AlC 3 The total density of states TDOS before .
[0055] Fig. 20 Shows Ta 2 O 5 / Nb 2 AlC sensor adsorbs NH 3 Comparison chart of TDOS before and after.
[0056] Fig.21 Shows Ta 2 O 5 / Nb 2 AlC sensor adsorbs NH 3 Projected density of states (PDOS) diagram of a molecule.
[0057] Fig. 22 Shows Ta 2 O 5 / Nb 2 AlC composites for NH 3 Schematic diagram of the sensing mechanism.
[0058] Fig.23 The structural schematic diagram of TENG is shown.
[0059] Fig.24 The curve of the peak current of TENG changing with the rotation speed is shown.
[0060] Fig.25 The voltage curves of TENG at different rotation speeds are shown.
[0061] Fig.26 The curve showing the change of the peak-to-peak value of the open-circuit voltage of TENG with the rotation speed.
[0062] Fig. 27 The voltage curve of TENG at a rotation speed of 55 rpm is shown.
[0063] Fig.28 The current curve of TENG at a rotation speed of 55 rpm is shown.
[0064] Fig.29 The curves showing the peak voltage and current of the external resistor as a function of the resistance value are shown.
[0065] Fig.30 The curve of the peak power of TENG changing with the resistance value of the external load is shown.
[0066] Fig.31 The voltage curve of TENG charging a 470μF capacitor is shown.
[0067] Fig.32 The voltage durability of TENG is shown.
[0068] Fig.33Shows NH 3 The voltage change curve on the energy storage capacitor when the concentration monitoring system is working.
[0069] The reference numerals in the above drawings are:
[0070] 10. Rotor; 20. Stator; 21. First copper electrode; 22. Second copper electrode; 30. Mechanical shaft. DETAILED DESCRIPTION
[0071] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] A kind of Ta 2 O 5 / Nb 2 The preparation method of the AlC composite ammonia sensor specifically comprises the following steps:
[0073] S1, 10 mL, 1.6 mol NH 4 F aqueous solution and 10 mL, 0.2 mol (NH 4 ) 2 S 2 O 8 The aqueous solution was mixed and stirred for 0.5 h, and 0.4 g (NH 4 ) 2 SO 4 , to obtain mixture A.
[0074] S2, transfer the mixture A to a 30 mL Teflon high-pressure reactor, put a Ta substrate with a purity of 99.99% into the solution, and obtain a mixture B.
[0075] S3, heating the mixture B to 200°C for 48h to form Ta on the Ta substrate 2 O 5 The membrane was separated from the liquid phase and washed with deionized water to obtain product A, which was dried at room temperature overnight to obtain Ta 2 O 5 .
[0076] S4, Nb was synthesized from 99.9% pure, 4.5μm Nb, 99.8% pure, 12.8μm Al and 99.8% pure, 8.5μm NbC powders. 2 AlC.
[0077] S5, preparation of complex Ta 2 O5 / Nb 2 AlC.
[0078] S6, using the complex Ta 2 O 5 / Nb 2 Preparation of Ta from AlC 2 O 5 / Nb 2 AlC composite ammonia sensor.
[0079] Specifically, step S4 includes the following steps:
[0080] S4.1, a mixture C having a molar ratio of Nb:Al:NbC=2:1.2:1 is mixed in ethanol for 24 hours.
[0081] S4.2, in a graphite mold pre-sprayed with a layer of boron nitride BN, uniaxial compaction was performed at 20 MPa, and finally vacuum sintering was performed in a spark plasma sintering system to obtain sample A.
[0082] S4.3, after sintering, cool sample A to room temperature, and use a fine sand high-speed diamond grinding wheel to mechanically process the surface of the sintered sample A to remove the layer contaminated by the carbon sheet, thereby obtaining Nb 2 AlC.
[0083] Specifically, the processing parameters in step S4.2 are set as follows:
[0084] The heating temperature is 1450℃ and the SPS chamber is evacuated to 10 -2 Pa, heating rate 100℃ / min, mechanical pressure 30MPa. External pressure was applied continuously from the beginning to the end of heating, and the heating time was 8 minutes. The temperature was measured with an optical pyrometer through the hole in the graphite mold.
[0085] Specifically, step S5 includes the following steps:
[0086] S5.1, use a volume ratio of 3:1 H 2 SO 4 -HNO 3 The mixture was treated at 60 °C for 5 hours. 2 AlC, Nb 2 AlC surface functionalization;
[0087] S5.2, 100 mg of functionalized Nb 2 AlC was dispersed in 50 mL of ethanol by ultrasonication for 0.5 h to obtain Nb 2 AlC solution; at the same time, 300 mg Ta 2 O 5Dispersed in a mixture of 140 μL benzyl alcohol and 10 mL anhydrous ethanol and added to Nb 2 AlC solution, solution A is obtained;
[0088] S5.3, pre-purge with nitrogen for 0.5 h to remove dissolved oxygen in solution A and stir for 12 h, then transfer the mixture into a microwave reactor and store at 150 °C for 1 h;
[0089] S5.4, after cooling, filter the precipitate, wash with ultrapure water, and dry in a vacuum oven at 80°C for 8 h to obtain the complex Ta 2 O 5 / Nb 2 AlC.
[0090] Specifically, step S6 includes the following steps:
[0091] S6.1, Ta 2 O 5 / Nb 2 The AlC solution was dropped onto the polyimide substrate to form a sensing film through interdigital electrodes;
[0092] S6.2, after vacuum drying at 60 °C for 4 h, Ta 2 O 5 / Nb 2 AlC composite ammonia sensor.
[0093] Specifically, the size of the Ta substrate in step S2 is: 10×10×0.25 mm.
[0094] Next, Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 AlC composites were analyzed: Scanning electron microscopy (SEM) was used to characterize the Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 Surface morphology of AlC composites. Figure 1 It can be seen that the etched Nb 2 AlC nanosheets present an accordion-like layered structure. This multi-layered sheet structure has a large lateral size and a large adsorption surface area. Figure 2 Shows the prepared Ta 2 O 5 The material is in rod shape. Figure 3 As shown in Ta 2 O5 / Nb 2 In AlC composites, Ta 2 O 5 Nanorods are interlaced in Nb 2 In AlC nanosheets. Figure 4 As shown in the enlarged Figure 3 The SEM image of Nb 2 Ta on AlC nanolayers 2 O 5 Nanorods.
[0095] From Ta 2 O 5 and Nb 2 Many diffraction peaks can be seen in the X-ray diffraction (XRD) pattern of AlC material within the scanning range of 10° to 80°. Figure 5 As shown, the characteristic peaks observed at 13.0°, 25.8°, 33.5°, 34.2°, 38.9°, 42.7°, 47.2°, 52.3°, 57.9°, 59.6°, and 65.9° correspond to Nb 2 The (002), (004), (100), (101), (102), (006), (104), (105), (106), (107) and (110) planes of AlC match the standard pattern (JCPDF#00-030-0033). 2 O 5 It exhibits an orthorhombic crystal orientation, and its diffraction peaks at 2θ=22.97°, 28.43°, 36.83°, 46.77°, 49.94°, 50.85° and 55.61° correspond to (001), (1110), (1111), (002), (0220), (2151) and (1112) planes, respectively. 2 O 5 The orthorhombic (β) phase belongs to the P21212 space group, with lattice constants a = 0.6198nm, b = 4.029nm, c = 0.3880nm, α = β = γ = 90°. The XRD peaks are clear, with no extraneous peaks or obvious background interference, indicating that the synthesized Ta 2 O 5 and Nb 2 AlC has a high phase purity. In addition, the strong peak intensity and narrow width indicate that the material has a relatively large grain size and good crystallinity. No additional impurity peaks were detected in the current spectrum, confirming the high purity of these two materials. 2 O 5 The Fourier transform infrared (FTIR) spectrum of the sample showed that the spectrum was at 565 cm -1The absorption bands at the NbO-Ta and Ta-O stretching are mainly attributed to the 2 The FTIR spectrum of AlC is at 483 cm -1 The absorption bands appearing in the band are attributed to the Nb-C bond, which is also the Nb 2 Characteristic peaks of AlC materials. Figure 7 As shown, Ta 2 O 5 / Nb 2 The FTIR absorption peak of AlC composites includes Ta 2 O 5 and Nb 2 Characteristic peaks of AlC samples. Figure 6 As shown, Ta 2 O 5 The Raman spectrum shows 265cm -1 and 220cm -1 The peaks at 400 to 800 cm-1 correspond to the bending and vibration of Ta-Ta polyhedrons. -1 The Raman band between corresponds to Ta 2 O 5 Symmetric O-Ta vibrations in octahedron. Nb 2 AlC material at 267cm -1 The Raman peak at is attributed to the vibration mode of Nb atoms. Figure 6 As shown, Ta 2 O 5 and Nb 2 The Raman peaks of the two materials AlC also appear in Ta 2 O 5 / Nb 2 AlC composites.
[0096] The sensor was placed in dry NH 3 After 60 seconds of stabilization in the environment, place it in a dry air environment (0ppmNH 3 ) for 60s to restore its resistance. 3 The resistance value in the environment is defined as the base resistance. 2 AlC composites and pure Ta based 2 O 5 The base resistance of the sensor of the material is 180MΩ and 1401MΩ, respectively, which indicates that the doped Nb 2 The resistance of the sensor after AlC is lower. The sensor with reduced resistance is more conducive to adapting to the circuit for monitoring. 2 O 5 and Ta 2 O 5 / Nb 2AlC sensor in NH 3 The resistance value in the environment decreases. Figure 8 and Fig. 9 As shown in the figure, the resistance values of the two sensors increase with NH 3 In order to better compare the performance of the sensor, the resistance change of the sensor is normalized to the response S.
[0097] The response S is calculated as follows:
[0098]
[0099] Among them, R g The sensor is at a certain concentration of NH 3 The resistance under R a The sensor is at 0ppm NH 3 The response of both sensors is as NH 3 The concentration increases gradually. Fig.10 and Fig.11 As shown, Ta 2 O 5 / Nb 2 The response of AlC sensor is higher than Ta 2 O 5 sensor, which indicates that Ta 2 O 5 / Nb 2 AlC materials have better NH 3 Sensing effect. 2 AlC sensor for NH 3 The response is close to 0%. 2 AlC and Ta 2 O 5 The increase in mass ratio, Ta 2 O 5 / Nb 2 AlC composites for 7 ppm NH 3 The response of Nb increases first and then decreases. 2 AlC and Ta 2 O 5 The maximum response is achieved when the mass ratio of Nb is 1:3. 2 AlC and Ta 2 O 5 The synergistic effect between Nb 2 AlC itself is NH 3 The sensitivity is not high, and the excess Nb 2 AlC will lead to a decrease in the reaction of the composite material to ammonia. Therefore, subsequent experiments use Nb 2 AlC and Ta2 O 5 Composite material with a mass ratio of 1:3.
[0100] like Fig.12 As shown, Ta 2 O 5 and Ta 2 O 5 / Nb 2 The response of AlC sensor is related to NH 3 The concentrations show a certain fitting relationship, and the fitting formulas are Y=104.13-103.52*0.95 X and Y = 68.61-71.54*0.82 X Their fitting coefficient R is as high as 0.99 2 The accuracy of the fitting formula is clarified. Response / recovery time is an important indicator to characterize sensor performance. Response / recovery time refers to the time taken for the response value to rise from a stable response value to 90%, and the time taken for the stable response value to drop to 10%. Fig.13 As shown, Ta 2 O 5 and Ta 2 O 5 / Nb 2 The response time of the AlC sensor at 7 ppm was 13 s and 5 s, and the recovery time was 43 s and 12.5 s, respectively. 3 Sensor comparison, Ta manufactured by the present invention 2 O 5 / Nb 2 AlC sensors have certain advantages in terms of response and response / recovery time, as shown in Table 1.
[0101] Table 1 Ta proposed in the present invention 2 O 5 / Nb 2 AlC sensor and NH 3 Sensor performance comparison
[0102]
[0103] like Fig.14 As shown, Ta 2 O 5 / Nb 2 The resistance of the AlC sensor is linearly related to temperature, and the fitting formula is Y = 0.2631X + 173.49. At room temperature, the resistance of the sensor increases slightly with the increase of temperature. In order to study the interference of relative humidity (RH) changes on the sensor, Ta 2 O 5 / Nb2 The response of the AlC sensor was also measured. Fig.15 As shown, at 0ppm NH 3 At concentrations, humidity changes can have a maximum impact of 8% on the sensor response, which can be offset by humidity sensor correction. Fig.16 As shown, at a concentration of 5 ppm, Ta 2 O 5 / Nb 2 AlC sensor is sensitive to acetone, nitrogen dioxide, hydrogen sulfide, sulfur dioxide, carbon monoxide and NH 3 The experimental results show that the sensor responds to NH 3 The response is the highest. Fig.17 As shown, at 1ppm and 11ppm, two NH 3 Ta was tested at concentrations 2 O 5 / Nb 2 Repeatability of AlC sensor. In the three repeatability tests, the response value did not change much. Fig.18 As shown, at 1ppm, 5ppm and 9ppm three NH 3 Concentration, test Ta 2 O 5 / Nb 2 Long-term stability of the AlC sensor. The results show that the sensor response deviation is less than 5%.
[0104] To further explore the 2 O 5 / Nb 2 AlC composites as NH 3 The mechanism of the sensing material is simulated using density functional theory (DFT). 3 After adsorption 2 O 5 , Nb 2 AlC and Ta 2 O 5 / Nb 2 Charge density maps of AlC materials to see the difference in charge distribution between the surface and surrounding areas of these materials. 2 O 5 , Nb 2 AlC and Ta 2 O 5 / Nb 2 The charge density distribution of AlC affects the NH 3 The interaction between molecules and the surface of materials. 2 O 5 / Nb 2The higher charge density of AlC indicates that the material surface has stronger polarity or higher charge transfer ability, which enables more efficient adsorption of NH 3 Molecule. Adsorption energy E ads Calculated according to the following formula:
[0105] E ads =E tot –E base –E gas
[0106] Among them, E tot 、E base and E gas The materials adsorb NH 3 The total energy of the gas molecules, the energy of the material itself and NH 3 The energy of the gas molecules. In addition, E ads The more negative the value, the more NH 3 The easier it is for gas molecules to react with NH 3 The better the adsorption effect of gas molecules, the better the charge density difference. As shown in Table 2, Ta 2 O 5 , Nb 2 AlC and Ta 2 O 5 / Nb 2 AlC E ads are -1.28eV, -1.52eV and -1.614eV respectively, which indicates that Ta 2 O 5 / Nb 2 AlC composites for NH 3 The adsorption capacity is higher than that of Nb 2 AlC and Ta 2 O 5 Even better. 2 O 5 / Nb 2 In the AlC composite, there may be stronger electron transfer or surface polar interaction, which makes NH 3 The molecules are more likely to form a stable adsorption structure on the surface of the material. Compared with the individual materials, this surface-enhanced adsorption capacity makes the composite material show stronger NH 3 Sensing performance.
[0107] Table 2Ta 2 O 5 ,Nb 2 AlC and Ta 2 O 5 / Nb 2 Adsorption parameters of AlC
[0108]
[0109] In addition, 2 O 5 , Nb 2 AlC and Ta 2 O 5 / Nb 2 The total density of states (TDOS) of the three AlC materials show that Fig.19 As shown, due to Nb 2 Doping of AlC materials, Ta 2 O 5 / Nb 2 The electron density curve of AlC is 2 O 5 Move to the left. Fig. 20 As shown, NH 3 After adsorption, Ta 2 O 5 / Nb 2 The electron density peaks in the TDOS diagram of AlC are slightly weakened in many places. 2 O 5 / Nb 2 The changes in the projected density of states (PDOS) curve of AlC materials are mainly attributed to the interactions between Nb 3d orbitals, Ta 3d orbitals, Al 2p orbitals, C2p orbitals, and O 2p orbitals. Fig.21 As shown, these orbitals have obvious overlapping peaks at 1.74 eV, -1.91 eV, -3.76 eV, and -8.4 eV, which indicates that NH 3 Molecules and Ta 2 O 5 / Nb 2 There is a strong hybridization between AlC composites.
[0110] Ta 2 O 5 As a wide-bandgap semiconductor oxide, it interacts with water vapor and oxygen molecules in the air to form hydroxyl groups (-OH) adsorbed on the surface. These -OH groups can react with NH 3 A chemical reaction occurs, releasing electrons to Ta 2 O 5 conduction band, thereby reducing Ta 2 O 5 The resistance of the material. Nb 2 AlC materials have a very high specific surface area, which can provide more active sites for adsorption of NH 3 At the same time, Nb 2 The two-dimensional layered structure of AlC can provide more paths to accelerate electron transmission and improve signal transmission efficiency. 2 O5 After compounding with MXene, the advantages of both can be fully utilized. 2 O 5 provides the basis for the active sites and resistance changes of the reaction with NHx, Nb 2 The excellent conductivity of AlC material helps to quickly conduct Ta 2 O 5 The composite material not only increases the electron change caused by the NH 3 The reaction sites can also respond quickly to the detected signal changes. Fig. 22 As shown in Figure 2, the synergistic effect of the two can significantly improve the performance of the sensor, making it have higher sensitivity, selectivity and response speed. The Nb 2 AlC、Ta 2 O 5 and Ta 2 O 5 / Nb 2 Nitrogen adsorption / desorption isotherms of AlC materials. The recorded data were analyzed using the BET method to determine the specific surface area of each material. 2 The BET surface area of AlC is 13.2 m 2 / g,Ta 2 O 5 6.7m 2 / g and Ta 2 O 5 / Nb 2 AlC is 53.5m 2 / g. These results show that compared with other materials, Ta 2 O 5 / Nb 2 AlC exhibits a significantly higher specific surface area, which suggests that it has potential for applications that benefit from the increased surface area.
[0111] Specifically, the prepared Ta 2 O 5 / Nb 2 AlC composite ammonia sensor is used in vegetable greenhouse self-powered NH 3 In the concentration monitoring system, NH 3 The concentration monitoring system includes: TENG, rectifier module, buck module, energy storage capacitor, voltage management module, Ta 2 O 5 / Nb 2AlC composite ammonia sensor, data acquisition module, wireless transmission module and real-time monitoring alarm module, after the rectifier module rectifies the alternating current of TENG into direct current, the step-down module then reduces the voltage and increases the current of TENG, and then stores the electrical energy in the energy storage capacitor, and then transmits the electrical energy to Ta through the voltage management module. 2 O 5 / Nb 2 AlC composite ammonia sensor, data acquisition module, wireless transmission module and real-time monitoring alarm module. The data acquisition module collects Ta 2 O 5 / Nb 2 The monitoring data of the AlC composite ammonia sensor is then transmitted to the real-time monitoring alarm module through the wireless transmission module.
[0112] Specifically, TENG is a barrel-shaped rotating free-standing structure. TENG includes: a rotor 10 and a stator 20. The stator includes: a first copper electrode 21 and a second copper electrode 22. The number of the first copper electrodes and the second copper electrodes is equal and there are multiple first copper electrodes and multiple second copper electrodes are distributed in a forked finger-like manner. The multiple first copper electrodes are connected to each other, and the multiple second copper electrodes are connected to each other. The first copper electrodes and the second copper electrodes are both covered on the inner wall of the barrel body of the acrylic substrate. The rotor is a plurality of capton films, and the plurality of capton films are distributed in the shape of fan blades. The plurality of capton films cover all the copper electrodes. One end of the capton film is connected to the mechanical shaft, and the other end contacts the stator. The mechanical shaft 30 is located at the center of the barrel body.
[0113] Specifically, there are 6 first copper electrodes, 6 second copper electrodes, and 4 capton films.
[0114] Specifically, the diameter of the TENG is 16 cm and the length of the barrel is 20 cm.
[0115] In order to capture the breeze energy around the vegetable greenhouse and provide wireless NH 3 Power supply for concentration monitoring system. Fig.23As shown, the present invention manufactures a barrel-shaped rotating free-standing TENG, which is based on the working principle of the coupling effect of contact electrification and electrostatic induction. In the initial state, the top capton film is aligned with the bottom first copper electrode. Due to the difference in the binding ability of the two materials to electrons, a large amount of negative charge will be generated on the surface of the top capton film. At the same time, an equal amount of positive charge will be generated on the surface of the bottom first copper electrode. At this time, the entire TENG is in an electrostatic equilibrium state, and no free electrons flow through the external circuit. As the rotor rotates, the top capton film moves to the right, and its overlapping area with the first copper electrode decreases and gradually overlaps with the second copper electrode. The potential difference generated will drive electrons from the second copper electrode to the first copper electrode, thereby generating a current from left to right in the external circuit. As the rotor continues to rotate, the capton film will completely cover the second copper electrode, and the entire system will reach an electrostatic equilibrium state, and no current will flow through the external circuit. Continue to rotate, the area where the capton film overlaps with the second copper electrode gradually decreases, and the potential difference will drive the circuit to generate opposite currents. As the rotation continues, the system will reach a state of electrostatic equilibrium again, and in this reciprocating manner, a continuous alternating current will be generated in the external circuit.
[0116] like Fig.24 As shown in Figure 2, when the rotation speed of TENG increases from 15 rpm to 75 rpm, the peak value of short-circuit current (Isc) gradually increases from 8.7 μA to 28.1 μA. The Isc of TENG increases almost linearly with the increase of rotation speed. Fig.25 As shown in Figure 2, the open circuit voltage (Voc) of TENG gradually increases in the speed range of 15-75 rpm. Fig.26 As shown in the figure, however, as the speed increases, the rate of increase of Voc gradually slows down, which is due to the faster dissipation of charge under high-frequency contact. Fig. 27 and Fig.28 As shown in the figure, the Voc and Isc of TENG at 55rpm show very regular periodic alternating current, which shows that TENG is very regular. In order to characterize the impedance and output power of TENG, the voltage of the external resistor on TENG and the current in the circuit are tested. Fig.29 As shown in the figure, the voltage, current and external resistance are positively correlated and negatively correlated respectively. Fig.30 As shown in Figure 2, according to the voltage and current calculation, when the load resistance is 750MΩ, the output power of TENG reaches a maximum value of 8.2mW. Fig.31 As shown in the figure, in order to characterize the charging effect of TENG, the voltage of TENG charging a 470μF capacitor after rectification and voltage reduction was tested. After 120s of charging, the voltage of the capacitor reached 15V. Fig.32As shown in Figure 2, after 2 hours of endurance test, the open circuit voltage of TENG decayed only a little. After 125 hours of endurance test, the normalized Voc gradually decreased from 725V to 655V, a decrease of about 90%. This decrease may be caused by slight wear on the surface of the capton film.
[0117] As a self-powered sensor, Ta 2 O 5 / Nb 2 The AlC sensor was directly connected to the TENG and measured the NH 3 When the TENG was operated at 55 rpm, the voltage on the sensor changed with the change of NH3 concentration, which showed that this voltage could be used as a proxy for NH 3 The sensor signal of concentration. In the case of breeze driving, the power of TENG is not enough to fully supply the sensor, data acquisition module and wireless transmission module. Therefore, the present invention designs a self-starting module, which can store the power of TENG and release energy to supply the data acquisition module and wireless transmission module when the power is sufficient, thereby realizing a completely self-powered NH 3 Sensing and wireless transmission. The self-starting module includes: a rectifier module, a step-down module, an energy storage capacitor, and a voltage management module. After the alternating current of TENG is rectified into direct current by the rectifier bridge in the rectifier module, the voltage of TENG is reduced and the current is increased through the step-down circuit in the step-down module, and stored in the energy storage capacitor C2. The voltage management module for reducing voltage and increasing current consists of a switch formed by a silicon-controlled rectifier (SCR), an inductor L=2.2mH, and a parallel diode D1. When the voltage in the capacitor reaches 5.3V, the voltage management module will supply electrical energy to the back-end data acquisition module and the wireless transmission module R2. Fig.33 As shown in Figure 2, at a rotation speed of 50 rpm, the developed system can achieve a NH emission every 70 seconds. 3 The data acquisition module mainly uses the analog-to-digital converter (ADC) function of the STM32L031 microcontroller, while the wireless transmission is achieved through a 433MHz wireless transmitter. The real-time monitoring alarm module displayed on the computer can display the received NH in real time. 3 Sensor data and concentration over-limit alarm. Driven by motor, simulate environmental wind energy to drive TENG and test Ta 2 O 5 / Nb 2 AlC sensor in air and NH 3The data in the TENG is transmitted wirelessly to the computer. Without a motor, the system can be driven by wind energy in the environment, which rotates the fan blades on the TENG and powers the entire system. In the laboratory, we used a fan to simulate environmental wind energy and tested the interval time for the self-awakening system to continuously transmit sensor signals in the wind speed range of 3.8m / s to 8m / s. As the wind speed increases, the time required for the system to transmit sensor signals gradually decreases due to the increase in the rotation speed of the TENG.
[0118] In summary, this study developed a self-driven vegetable greenhouse NH 3 The monitoring system realizes intermittent NH3 concentration monitoring and alarm. Ta was prepared by physical composite method. 2 O 5 / Nb 2 AlC binary nanocomposite materials were prepared and their morphology, lattice and molecular structure were characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). On this basis, a NH 3 Sensor. By comparison, based on Ta 2 O 5 / Nb 2 The AlC material sensor shows better performance than single Ta 2 O 5 The DFT calculation results show that Ta 2 O 5 / Nb 2 AlC binary nanocomposites for NH 3 The adsorption performance is better than that of single Ta 2 O 5 and Nb 2 AlC material. Research has found that Ta 2 O 5 / Nb 2 Due to the synergistic effect of binary nanomaterials, the charge transfer in the AlC system is much better than that of single Ta 2 O 5 The system is stronger. 2 The two-dimensional structure of AlC provides more adsorption sites, thus enhancing the NH 3 In addition, the developed barreled TENG uses the breeze energy in the environment to power the system, and designs a self-starting system to periodically release electrical energy to start the data acquisition and wireless transmission system, thereby realizing the NH 3 Real-time monitoring and alarm of concentration. This study provides a self-powered trace NH 3 Monitoring provides innovative solutions and promotes the rapid development of modern agriculture.
[0119] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor, characterized in that: The specific steps include: S1, 10 mL of 1.6 mol NH4F aqueous solution and 10 mL of 0.2 mol (NH4)2S2O8 aqueous solution were mixed and stirred for 0.5 h, and 0.4 g (NH4)2SO4 was added during the stirring process to obtain a mixture A; S2, transfer the mixture A into a 30 mL Teflon autoclave, place a Ta substrate with a purity of 99.99% into the solution, and obtain a mixture B; S3, heating the mixture B to 200°C for 48 hours, separating the Ta2O5 film on the Ta substrate from the liquid phase, washing with deionized water to obtain product A, and drying the product A at room temperature overnight to obtain Ta2O5; S4, synthesizing Nb2AlC using 99.9% purity, 4.5 μm Nb, 99.8% purity, 12.8 μm Al and 99.8% purity, 8.5 μm NbC powders as raw materials; S5, preparation of composite Ta2O5 / Nb2AlC; S6, using the composite Ta2O5 / Nb2AlC to prepare a Ta2O5 / Nb2AlC composite ammonia sensor.
2. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 1, characterized in that: Step S4 specifically includes the following steps: S4.1, mixing a mixture C having a molar ratio of Nb:Al:NbC=2:1.2:1 in ethanol for 24 hours; S4.2, in a graphite mold pre-sprayed with a layer of boron nitride BN, uniaxial compaction at 20 MPa was performed, and finally vacuum sintering was performed in a spark plasma sintering system to obtain sample A; S4.3, after sintering, sample A is cooled to room temperature, and the surface of the sintered sample A is machined using a fine sand high-speed diamond grinding wheel to remove the layer contaminated by the carbon flakes, thereby obtaining Nb2AlC.
3. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 2, characterized in that: The processing parameters in step S4.2 are set as follows: The heating temperature is 1450℃ and the SPS chamber is evacuated to 10 -2 Pa, the heating rate is 100℃ / min, and the mechanical pressure is 30Mpa; the external pressure is continuously applied from the beginning to the end of heating, and the heating time is 8 minutes.
4. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 3, characterized in that: Step S5 includes the following steps: S5.1, treating Nb2AlC with a H2SO4-HNO3 mixture with a volume ratio of 3:1 at 60 °C for 5 h to functionalize the Nb2AlC surface; S5.2, 100 mg of functionalized Nb2AlC was dispersed in 50 mL of ethanol by ultrasonication for 0.5 h to obtain a Nb2AlC solution; at the same time, 300 mg of Ta2O5 was dispersed in a mixture of 140 μL of benzyl alcohol and 10 mL of anhydrous ethanol, and added to the Nb2AlC solution to obtain solution A; S5.3, pre-purge with nitrogen for 0.5 h to remove dissolved oxygen in solution A and stir for 12 h, then transfer the mixture into a microwave reactor and store at 150 °C for 1 h; S5.4, after cooling, filter the precipitate, wash with ultrapure water, and vacuum dry it in a vacuum drying oven at 80°C for 8 h to obtain the composite Ta2O5 / Nb2AlC.
5. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 4, characterized in that: Step S6 includes the following steps: S6.1, dropping Ta2O5 / Nb2AlC solution onto a polyimide substrate to form a sensing film through interdigital electrodes; S6.2, after vacuum drying at 60°C for 4 h, the Ta2O5 / Nb2AlC composite ammonia sensor was obtained.
6. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 5, characterized in that: The size of the Ta substrate in step S2 is: 10×10×0.25 mm.
7. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 6, characterized in that: The prepared Ta2O5 / Nb2AlC composite ammonia sensor is applied to the self-powered NH3 concentration monitoring system of the vegetable greenhouse. The NH3 concentration monitoring system includes: TENG, a rectifier module, a step-down module, an energy storage capacitor, a voltage management module, a Ta2O5 / Nb2AlC composite ammonia sensor, a data acquisition module, a wireless transmission module and a real-time monitoring alarm module. After the alternating current of TENG is rectified into direct current by the rectifier module, the voltage of TENG is reduced and the current is increased by the step-down module, and then the electric energy is stored in the energy storage capacitor, and then the electric energy is transmitted to the Ta2O5 / Nb2AlC composite ammonia sensor, the data acquisition module, the wireless transmission module and the real-time monitoring alarm module by the voltage management module. The data acquisition module collects the monitoring data of the Ta2O5 / Nb2AlC composite ammonia sensor, and then transmits the monitoring data to the real-time monitoring alarm module by the wireless transmission module.
8. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 7, characterized in that: TENG is a barrel-shaped rotating free-standing structure. TENG includes: a rotor and a stator. The stator includes: a first copper electrode and a second copper electrode. The first copper electrode and the second copper electrode are equal in number and are multiple. The multiple first copper electrodes and the multiple second copper electrodes are distributed in a forked finger-like manner. The multiple first copper electrodes are connected to each other, and the multiple second copper electrodes are connected to each other. The first copper electrodes and the second copper electrodes are both covered on the inner wall of the barrel body of the acrylic substrate. The rotor is a plurality of capton films. The plurality of capton films are distributed in the shape of fan blades and cover all the copper electrodes. One end of the capton film is connected to the mechanical shaft, and the other end contacts the stator. The mechanical shaft is located in the center of the barrel body.
9. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 8, characterized in that: There are 6 first copper electrodes, 6 second copper electrodes, and 4 capton films.
10. The method for preparing a Ta2O5 / Nb2AlC composite ammonia sensor according to claim 9, characterized in that: The diameter of TENG is 16 cm and the length of the barrel is 20 cm.